The Effect of Scaffolding Techniques on Students’ Writing Achievement - Yulia Vonna; Nur Mukminatien; Ekaning Dewanti Laksmi (Pascasarjana UM, 2015)
Abstract: This paper reports a study which investigated the effect of scaffolding techniques on students’ writing achievement. This study is quasi-experimental research with nonrandomized control group design. The total number of participants was 36 students who were in two different groups: experimental group and control group. There were twenty students in the experimental group and sixteen students in the control group. The result of the pre-test showed that both the experimental group and the control group were equal and homogenous since the statistical computation yielded significant value p = 0.890 which was higher than α =0.05. The analysis of writing test in post-test yielded p= .027 which was smaller than α = 0.05. Thus, it can be concluded that scaffolding techniques can significantly improve the students’ writing achievement.Key Words: scaffolding techniques, writing achievement Abstrak: Penelitian ini bertujuan untuk menginvestigasi teknik scaffolding terhadap kemampuan menulis siswa. Penelitian ini menggunakan eksperimental semu dengan desain nonrandomized control group. Jumlah partisipan dalam penelitian ini adalah 36 siswa yang dibagi dalam dua kelompok yaitu grup eksperimental dan grup kontrol. Grup eksperimental berjumlah 20 siswa, sedangkan grup kontrol berjumlah 16 siswa. Hasil pretest menunjukkan bahwa kedua grup sama dan homogen yang ditunjukkan oleh perhitungan statistik p = 0.890 yang lebih besar dari α =0.05. Sedangkan posttest menghasilkan p= .027 yang lebih kecil dari α = 0.05. Oleh karena itu dapat disimpulkan bahwa teknik scaffolding secara signifikan meningkatkan kemampuan menulis siswa.Kata kunci: teknik scaffolding, kemampuan menulis